Can recognition using LABVIEW / Jamilah Othman - Othman, Jamilah (2008)
This project presents the cans recognition using LABVIEW software. The importance of this recognition is to analysis of the object pattern and its ability to detect cans whether it under specification. The method that has been implemented is template pattern matching. There are numerous applications of template pattern matching techniques such as in industrial inspection, biomedical inspection and face recognition [5] .This project is to recognize two dimensional (2D) image using template pattern matching methods and integrate with Graphical User Interface (GUI). The software that has been used in this project is NI Vision and LABVIEW. LABVIEW is a graphical programming language to develop complex measurement and control applications very quickly and easily. LABVIEW is used to develop Graphical User Interface and NI Vision is used for image processing.